Mastering JMeter 5.0 - Atar, Afsana (Packt Publishing, 2020)
A comprehensive guide to automating performance measurement for your website and web applications using JMeter 5.0 About This Video Provides in-depth knowledge of the advanced features of JMeter including assertions, controllers, and validations Learn to integrate JMeter with web testing tools such as Selenium to extend web testing capabilities and measure web application performance Use the latest version of the JMeter tool for test monitoring and reports In Detail JMeter has become an industry-standard tool for conducting functional, load, performance, and regression tests on web applications. It scales web development by helping you measure and analyze application performance. In this course, you'll learn to invoke key features of the latest version of this testing tool to achieve peak performance for your web applications, all the while improving the testing team's productivity by developing realistic and scalable test plans and automation. You'll start by mastering assertion types and scripts. Then you'll immerse yourself in the world of logic controllers and apply them to scripting. You'll get to grips with samplers, which help you send a request to the web server. You'll learn advanced scripting, work with test controllers, design test plans, and much more. By the end of this course, you will be able to use JMeter 5.0 for performance and load testing.